توكيد الذات وعلاقته بالذكاء لدى تلاميذ الصف السادس الاساسي الحكومي – الاهلي وفق بعض المتغيرات - يحيى, بان صباح (Sulaimani Journal for Humanities, 2018)
This research aims to define self proving and its relation to the intelligence of a sample of essential sixth grade students in the governmental and private schools, the researcher has prepared a scale for self proving depending on literatures and previous studies, it consists of (26) items, but for the intelligence test she depended the test of (Martin Lother Joahan) which was translated by Izzaddin Al-Ashoul (1982), the scale of self proving has been applied on (256) essential sixth grade students in the governmental and private schools (m and f) and has been tested randomly according to the moms estimation and the teachers, the schools have been selected randomly, and the research has reached the following points:- The level of self proving of the students of the essential sixth grade in the governmental and private schools is high according to the estimation of the moms and teachers, the result of the estimation has shown high evaluation of self proving of the sample of the students in the governmental and private schools, the result has shown a differences in the intelligence quality of the students in the governmental and private schools, for the sake of the governmental students, and the estimation of the moms and the students has shown the existence of difference in both sexes between the research sample for the sake of the private school, and has not shown relational differences between the modulus of self proving related according to the estimation of the (moms and teachers) for the intelligence and sex of the students in the private and governmental schools.